Resource rents and inclusive human development in developing countries - Tii Njivukuh Nchofoung; Elvis Dze Achuo; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
This study aims to empirically verify the effects of natural resource rents on inclusive human development in developing countries. The results from the IV Tobit regression show that natural resource rents have a positive direct effect on inclusive human development in developing countries and that this relationship varies by regional groupings, income levels, level of development and export structure. Looking at the transmission mechanisms, when the interactive variables of governance and environmental quality is introduced, the modulating channel through governance exerts a robust negative synergy effect in the sample of developing countries and positive synergy effects for Africa and low-income countries. When the interactive variable of CO2 emissions is introduced for Africa, a negative net effect of natural resource rents on inclusive human development is obtained. This was up to a policy threshold of 25.4412 of CO2 emissions when the negative effect is nullified. For Asia and the Latin America and Caribbean, a positive net effect is obtained. This is up to a CO2 emissions threshold of 29.038 and 3.6752 respectively, when the positive effect is nullified. Besides, the high income and the upper-middle income countries produce a negative net effect of resource rents on inclusive human development through CO2 modulation, with up to positive CO2 emission thresholds of 37.9365 and 23.6257 respectively. Policy implications are highlighted. In summary, contingent on engaged specificities, where conditional effects are negative, negative thresholds for complementary policies have been provided and in scenarios where conditional impacts are positive, actionable positive thresholds have been provided.
Keywords: P48; O11; C23; 330; Resource Rents; Inclusive Human Development; Institutional Quality; Environmental Quality